Impact of Data Centers on Climate Change: A Review of Energy Efficient Strategies - Daniel Raphael Ejike Ewim; Nwakamma Ninduwezuor-Ehiobu; Ochuko Felix Orikpete; Blessed Afeyokalo Egbokhaebho; Akeeb Adepoju Fawole; Chiemela Onunka (The Journal of Engineering and Exact Sciences)
The rapid proliferation of digital services and the surge in cloud computing have significantly increased the demand for data centers worldwide. As these facilities consume vast amounts of energy, there is growing concern about their impact on the environment, particularly in relation to climate change. This paper reviews the extent to which data centers contribute to global greenhouse gas emissions and examines the energy efficient strategies being employed to mitigate their environmental footprint. Key findings indicate that without intervention, data centre emissions could rival those of major global industries. Fortunately, innovations in cooling technologies, architectural design, renewable energy sourcing, and hardware efficiency have shown potential in reducing energy consumption. The paper also underscores the importance of a holistic approach that encompasses both technological advancements and policy measures for meaningful progress. In conclusion, while data centers are indeed a source of climate concern, the ongoing advancements in energy-efficient strategies provide a promising pathway towards a sustainable digital future.